The Teaching Method of Imam Badr al-Din al-Aini on Hadith through His Commentary on Sahih al-Bukhari | تعليمية الحديث النبوي عند الإمام بدر الدين العيني من خلال شرحه على صحيح البخاري - Chettih Benyoucef (Al-Zahra : Journal for Islamic and Arabic Studies, 2020)
No one believes that the Western nations have done anything respectable in the field of teaching materials. It should not be denied. This is what is imposed on us by the objective scientific logic, but it is wrong and unfair to deny what is in our linguistic, literary and legal heritage from the seeds of their early position on education, teaching methods, Of the researchers prospecting and directing them to the people. It is among those who excelled in explaining the hadiths of the Prophet peace be upon him Imam Badr al-Din al-'Eini, where his explanation and the analysis of Al-Wafi is considered a model for the consolidation of the modern Hadith through the explanation of the encyclopedia on Saheeh Al-Bukhari and tagged as "the Mayor of the reader explained Sahih Bukhari," which is one of the most extensive and annotated, In this research I discover through the methodology in the explanation and analysis of some of the mechanisms and methods that dealt with the Prophet's speech, and that revealed the strategy and skills in the delivery and ability to influence and the techniques used in providing the subject of the learner in the easiest way, and the most effective way and how the teacher These steps are invested and adopted by these techniques in teaching Hadith to students.